Conversion to Reverse Total Shoulder Arthroplasty with and without Humeral Stem Retention: The Role of a Convertible-Platform Stem. (3rd May 2017) - Crosby, Lynn A.; Wright, Thomas W.; Yu, Stephen; Zuckerman, Joseph D.
Abstract : Background: Revision shoulder arthroplasty is a technically challenging procedure. It is associated with increased blood loss and operative time, and it frequently necessitates revision implants, augments, and bone-grafting. Shoulder arthroplasty systems with a convertible-platform humeral stem have been developed to reduce the complexity of revision procedures by eliminating the need for humeral component explantation when converting from anatomic shoulder arthroplasty (hemiarthroplasty or total shoulder arthroplasty) to reverse total shoulder arthroplasty (rTSA). Methods: A multicenter, retrospective analysis involving 102 consecutive shoulders (102 patients) that underwent revision of an anatomic shoulder arthroplasty to an rTSA was conducted. During the revision, 73 of the shoulders needed exchange of the humeral stem (the exchange group) and 29 had retention of a convertible-platform humeral component (the retention group). Patient demographics, operative time, blood management, range of motion, complications, and patient-reported outcomes were compared between the 2 groups. Results: Patients with retention had significantly shorter operative time (mean and standard deviation, 130 ± 48 versus 195 ± 58 minutes; p < 0.001) and lower estimated blood loss (292 ± 118 versus 492 ± 334 mL; p = 0.034). The rate of intraoperative complications was lower in the retention group (0% versus 15%; p = 0.027). Patients with retention had slightly better postoperative range of motion (active external rotation, 26° ± 23° versus 11° ± 23° [p = 0.006]; active forward elevation, 112° ± 37° versus 96° ± 33° [p = 0.055]). Conclusions: Shoulder arthroplasty systems that utilize a convertible-platform humeral stem offer an advantage for rTSA conversion in that a well-fixed, well-positioned humeral stem can be retained. There were significantly fewer complications as well as significantly decreased blood loss and operative time when a convertible-platform stem was utilized (p < 0.050). Level of Evidence: TherapeuticLevel III . See Instructions for Authors for a complete description of levels of evidence.